Fluvial architecture variations linked to changes in accommodation space: Río Chico Formation (Late Paleocene), Golfo San Jorge basin, Argentina - Foix, Nicolas (2013)
The Upper Paleocene Río Chico Formation is a 50-180. m thick fluvial succession developed in a passive-margin setting, Golfo San Jorge basin, Central Patagonia, Argentina. A detailed description and interpretation of outcrops was carried out, analyzing exposures from the northern basin margin to the most complete successions at the southern depocenter. The unit is characterized by a regional fluvial system that flowed to the south-east. Five main lithofacies associations were defined: (I) active fluvial channels, with three sub-types: braided, meandering and low-sinuosity, (II) sheet-flood deposits, (III) proximal floodplain (natural levee and crevasse-splay), (IV) distal floodplain, and (V) abandoned channels.Lateral/vertical changes in fluvial architecture of the Río Chico Formation were recognized by variations in preserved thickness, fluvial styles, geometry of fluvial channels, regional paleoflow directions, and channel/floodplain ratios. Close to the northern basin margin, the fluvial succession is 50-60. m thick, composed of braided channels, sheet-flow deposits, and high channel/floodplain ratio. In a basinward direction, the alluvial succession increases to 180. m in thickness, the dominant fluvial styles change to low-sinuosity and meandering channels and channel/floodplain ratio reduces.The fluvial architecture of the Río Chico Formation shows two main depositional trends that resulted from changes in accommodation space across the basin. The interpreted break-point coincides with the underlying Cretaceous basin-boundary, thus the synsedimentary extensional reactivation of the pre-existing tectonic lineament generated differential subsidence, delimiting two different accommodation settings.